Multibody System Dynamics, Robotics and Control - Gattringer, Hubert.; Gattringer, Hubert.; Gerstmayr, Johannes.; Gerstmayr, Johannes. (Springer Vienna : Imprint: Springer, 2013)
The volume contains 19 contributions by international experts in the field of multibody system dynamics, robotics and control. The book aims to bridge the gap between the modeling of mechanical systems by means of multibody dynamics formulations and robotics. In the classical approach, a multibody dynamics model contains a very high level of detail, however, the application of such models to robotics or control is usually limited. The papers aim to connect the different scientific communities in multibody dynamics, robotics and control. Main topics are flexible multibody systems, humanoid robots, elastic robots, nonlinear control, optimal path planning, and identification.